Effect of Excitation Wavelength on Optical Performances of Quantum-Dot-Converted Light-Emitting Diode - Caiman Yan; Xuewei Du; Jiasheng Li; Xinrui Ding; Zongtao Li; Yong Tang (Nanomaterials, 2019)
Light-emitting diode (LED) combined with quantum dots (QDs) is an important candidate for next-generation high-quality semiconductor devices. However, the effect of the excitation wavelength on their optical performance has not been fully explored. In this study, green and red QDs are applied to LEDs of different excitation wavelengths from 365 to 455 nm. The blue light is recommended for exciting QDs from the perspective of energy utilization. However, QD LEDs excited at 365 nm have unique advantages in eliminating the original peaks from the LED chip. Moreover, the green or red light excited by ultraviolet light has an advantage in colorimetry. Even for the 455 nm LED with the highest QD concentration at 7.0 wt%, the color quality could not compete with the 365 nm LED with the lowest QD concentration at 0.2 wt%. A 117.5% (NTSC1953) color gamut could be obtained by the 365 nm-excited RGB system, which is 32.6% higher than by the 455 nm-excited solution, and this can help expand the color gamut of LED devices. Consequently, this study provides an understanding of the properties of QD-converted LEDs under different wavelength excitations, and offers a general guide to selecting a pumping source for QDs.